Nest-site choice by loggerhead sea turtles as a risk-management adaptation to offset hatching failure by unpredictable storms and predators - Cassill, Deby L.; Watkins, Alison (Frontiers in Ecology and Evolution, 2022)
Introduction Along the coasts of Florida, United States, the nesting season of the loggerhead sea turtle, Caretta caretta, overlaps with the hurricane season. Nesting loggerhead females do not extend parental protection beyond depositing eggs in sandy, excavated nests in locations that provide a viable range of temperatures, moisture, and respiratory gas exchange. Thereafter, a female’s clutches are subjected to the uncertainties of desiccation, predation, flooding, or beach erosion. Methods Here, we used data from a 1996-2004 study of 94 tagged loggerhead females nesting on a small barrier island off the Gulf Coast of south Florida, United States. We tested the hypothesis that the distribution of nest sites by loggerhead females was a randomized response to unpredictable hatching failure. Results We show that nest site choice accounted for 19.2% of variation in hatching success whereas breeding year and breeding month accounted for the remaining 81.8% of variation in hatching success. We show that the emergence site along the beach-length axis, nest site choice along the beach-width axis, and distances between nest locations did not fit a uniform-random distribution or a normal distribution. Instead, we show that loggerhead females employed a “Goldilocks” distribution in which nest sites were “neither too clustered nor too dispersed.” Moreover, loggerhead females selected nest sites with limited overlap with nest sites from previous breeding seasons. Discussion We propose that nest site choice by this population of loggerhead females constitutes a significant maternal risk-management adaptation that deserves thoughtful consideration as we continue to assess the impacts of climate change on the future of loggerhead sea turtles.